Comparison of Elderlys \"Quality of Life\" Living at Homes and in Private or Public Nursing Homes - Ali Hesamzadeh; Sadat Bagher Maddah; Frahnaz Mohammadi; Masoud Fallahi Khoshknab; Mehdi Rahgozar (Sālmand, 2010)
Objectives: The aim of this study was to compare the quality of life and its dimensions among the elderly people who were living at homes, private or public nursing homes of the city of Tehran.